(untitled) (Journal of Information Technologies in Education (ITE), 2010)
This article deals methodological aspects forming divergative mentality for future teachers of math to process of preparation in the higher pedagogical schools and universities. Special attention give for progress characteristically abilities of future teachers. Creative mathematical tasks the effective way of the student’s activity formation take a special place.